(untitled) (International journal of artificial intelligence, 2026)
This article evaluates the structural significance of the industrial sector as a primary catalyst for sustainable economic growth. By synthesizing classical structuralist theories with contemporary technological paradigms, the study explores the mechanisms through which manufacturing stimulates aggregate demand, accelerates technological innovation, and enhances total factor productivity. Utilizing recent empirical data and modern economic literature, the paper highlights how industrialization acts as a growth driver, particularly within emerging markets undergoing digital transformation. The analysis offers a comprehensive view of industrial expansion, emphasizing that strategic policy interventions are essential to transition from labor-intensive production to high-value-added digital manufacturing.